Bacterial translocation and mortality on rat model of intestinal ischemia and obstruction - Costa,Rafael Izar Domingues da (2017)
Abstract Purpose: To develop an experimental model of intestinal ischemia and obstruction followed by surgical resection of the damaged segment and reestablishment of intestinal transit, looking at bacterial translocation and survival. Methods: After anesthesia, Wistar rats was subject to laparotomy, intestinal ischemia and obstruction through an ileal ligature 1.5cm of ileum cecal valve; and the mesenteric vessels that irrigate upstream of the obstruction site to approximately 7 to 10 cm were ligated. Abdominal wall was closed. Three, six or twenty-four hours after, rats were subject to enterectomy followed by an end to end anastomosis. After 24h, mesenteric lymph nodes, liver, spleen and lung tissues were surgically removed. It was studied survival rate and bacterial translocation. GraphPadPrism statistical program was used. Results: Animals with intestinal ischemia and obstruction for 3 hours survived 24 hours after enterectomy; 6hx24h: survival was 70% at 24 hours; 24hx24h: survival was 70% and 40%, before and after enterectomy, respectively. Culture of tissues showed positivity on the 6hx24h and negativity on the 3hx24h. Conclusion: The model that best approached the clinic was the one of 6x24h of ischemia and intestinal obstruction, in which it was observed bacterial translocation and low mortality rate.